Automatic Melody Composition Inspired by Short Melodies Using a Probabilistic Model and Harmonic Rules - Tardón-García, Lorenzo José; Barbancho-Pérez, Isabel; Barbancho-Pérez, Ana María; Roig, Carles; Tzanetakis, George (International Society for Music Information Retrieval (ISMIR), 2019)
This demo shows how automatic melody composition of melodies that follow the style of a certain singleshort melodic excerpt can be achieved in such a way that the sample excerpt can be considered an inspirationalpiece of music for the automatic compositor.Music composition has been faced from diverse perspectives and using different approaches, among them theutilization of probabilistic schemes is common since early stages. For example, Brooks et al. [1] considerthe direct utilization of m-order Markov chains for music analysis and generation, and other authors havefollowed a relatively similar path [2]. Often large data sets are necessary to train music generation systems,though in some rare cases algorithms are developed to perform automatic melody composition based on asingle sample melody [5]; in such case, the application of explicit rules is of great importance.Considering the probabilistic approach to music models and music rules on the basis of the melody generationmodel developed in [4], a melody generation scheme is designed that is capable of generating music excerptswith the style and resemblance of short individual MIDI melody samples.Since only one sample melody of arbitrarily small duration will be considered, some modification must bedone to the system described in [4]. Specifically, modifications are necessary in the extraction of musicalparameters and in the generation scheme in order to provide with the necessary musical variability for theadaptation of extracted musical parameters and patterns. .
Keywords: Música - Proceso de datos; Music Information Retrieval (MIR); Automatic Music Generation; Audio Signal Processing; Probabilistic Model